Adsorbate‐Induced Modifications in the Optical Response of the Si(553)–Au Surface. Issue 6 (9th May 2022) - Chandola, Sandhya; Sanna, Simone; Hogan, Conor; Speiser, Eugen; Plaickner, Julian; Esser, Norbert
Abstract : The conductivity of substrate‐supported metallic nanowires can be adjusted, e.g., by strain or adsorbates. In this article, the effect of atomic hydrogen and toluene‐3, 4‐dithiol (TDT) adsorption on the quasi‐1D structures of the Si(553)‐(5 × 2)–Au reconstruction is investigated. Reflectance anisotropy spectroscopy (RAS) and infrared ellipsometry reveal optical signatures of the surface. Spectral modifications related to the adsorbate exposure suggest the activation of adsorption‐induced interband transitions. Density functional theory (DFT) calculations reproduce the spectral modifications and explain their origin. Preferential adsorption on sites located at the step edges of the structure occurs independent of the type of adsorbate and induces a charge transfer between electronic states related to the step edges and the Au dimer rows. This charge redistribution modifies the electronic structure close to the Fermi level, enhances the dimerization of the Au chains, and strongly influences the low‐energy region of the RAS spectra. While previous studies employed atomic H as a chief adsorbate, it is shown here that even molecular H deeply modifies the Si(553)–Au optical response. Structural modification of Au–Si(553) by H and TDT adsorbates as suggested from recent ab initio calculations are verified. Abstract : Reflectance anisotropy spectroscopy (RAS) and infrared ellipsometry are particularly suited to identify the spectral features related to atomic‐scale structural motifs at surfaces or interfaces. Here, adsorbates on Au–Si(553) are studied by experiment and atomistic calculations. The adsorption occurs at the step edge and thereafter on the terrace. An adsorbate‐to‐substrate charge transfer modifies the chain structure. Accordingly, optical signatures are identified.